PRICE, PROMOTION, RELIABILITY, AND TANGIBLES INFLUENCE TOWARD SHOPEE e-COMMERCE PLATFORM PURCHASE INTENTION - Angelica, Gabrielle; Gunawan, Lenny (Accounting Study Program, Universitas Ciputra Surabaya, 2024)
The internet is now used in all facets of human existence, including in the trade aspects. Various websites or applications that provide consumer goods have evolved in response to these needs. Shopee marketplace is one of the e-commerce platform applications that exist globally. The focus of this research is customers’ purchasing decisions in the Shopee marketplace. Several factors influence purchasing decisions, but the researcher will focus on four variables only in this research study, namely price and promotion from the marketing mix approach, and reliability and tangibles from the service quality approach. The goal of this research was to see how price, promotion, reliability, and tangibles, have influenced purchasing decisions in the Shopee marketplace. This study takes a quantitative approach, with a questionnaire as the primary data collection tool. Purposive sampling theory was utilized to select 100 respondents for this investigation (respondents based on predetermined criteria). With the help of the SPSS program, the data acquired through the distribution of the questionnaire will be processed using multiple linear regression analysis techniques. The findings of this study show that the Price, Promotion, Reliability, and Tangibles have a strong beneficial effect on the purchasing decision variable partially and simultaneously.